Disonansi Kognitif Dalam Perilaku Konsumen Masyarakat Indonesia Terhadap Pembelian Produk Tanpa Logo Halal - Inke Nur Dewanti; Irwansyah Irwansyah (JURNAL LENSA MUTIARA KOMUNIKASI, 2021)
Product without halal certification still become pro and contra in Indonesia's people whose mostly Muslim. These phenomena cause cognitive dissonance in some of Indonesia's people consumer behavior. This dissonance happens because there are values and culture that influence the consumer behavior on products without halal certification buying process. With those phenomena, this research examines the dissonance process of buying the products without halal certification. The research method used is the literature review, using secondary data from scientific journals, books, and media articles. The result of this research shows that some of Indonesia's Muslims being worried if there's no halal certification because there is some difference in value & culture with the product.